Hydrophobic Mycobacterial Antigens Elicit Polyfunctional T Cells in Mycobacterium bovis Immunized Cattle: Association With Protection Against Challenge? - Benedictus, Lindert; Steinbach, Sabine; Holder, Thomas; Bakker, Douwe; Vrettou, Christina; Morrison, W. Ivan; Vordermeier, Martin; Connelley, Timothy (Frontiers in Immunology, 2020)
Bovine tuberculosis (bTB), caused by Mycobacterium bovis, is a chronic disease of cattle with a detrimental impact on food quality and production. Research on bTB vaccines has predominantly been focussed on proteinaceous antigens. However, mycobacteria have a thick and intricate lipid outer layer and lipids as well as lipopeptides are important for immune-evasion and virulence. In humans, lipid extracts of M. tuberculosis have been shown to elicit immune responses effective against M. tuberculosis in vitro. Chloroform-methanol extraction (CME) was applied to M. bovis BCG to obtain a hydrophobic antigen extract (CMEbcg) containing lipids and lipopeptides. CMEbcg stimulated IFN-γ+IL-2+ and IL-17A+IL-22+ polyfunctional T cells and elicited T cell responses with a Th1 and Th17 cytokine release profile in both M. bovis BCG vaccinated and M. bovis challenged calves. Lipopeptides were shown to be the immunodominant antigens in CMEbcg, stimulating CD4 T cells via MHC class II. CMEbcg expanded T cells killed CMEbcg loaded monocytes and the CMEbcg-specific CD3 T cell proliferative response following M. bovis BCG vaccination was the best predictor for reduced pathology following challenge with M. bovis. Although the high predictive value of CMEbcg-specific immune responses does not confirm a causal relationship with protection against M. bovis challenge, when taking into account the in vitro antimycobacterial phenotype of CMEbcg-specific T cells (e.g. Th1/Th17 cytokine profile), it is indicative that CMEbcg-specific immune responses could play a functional role in immunity against M. bovis. Based on these findings we conclude that lipopeptides of M. bovis are potential novel subunit vaccine candidates and that further studies into the functional characterization of lipopeptide-specific immune responses together with their role in protection against bovine tuberculosis are warranted.